Uma aplicação de programação inteira mista para o planejamento ótimo em operações de perfuração direcional - Fernandes, Clarissa Pessoa Borges (2024)
The growing demand for efficient and accurate methods in hydrocarbon exploration has driven the development of advanced directional drilling techniques. This thesis addresses this need by introducing an innovative application of Mixed Integer Programming (PIM) for optimal planning in directional drilling operations. Directional drilling is a fundamental technique for accessing oil reserves that would be inaccessible by conventional methods, but its planning requires a careful approach to maximize oil recovery and minimize operational costs. This study exploiting on identifying Hydraulic Flow Units (HFUs) within the reservoir, which are regions that share similar petrophysical properties and play a crucial role as targets of the drilling trajectory. The proposed methodology is based on two classical approaches from Optimization Theory the Traveling Salesman Problem (PCV) and the Team Orientation Problem (POE), both adapted to identify the best reference coordinates for the drilling route. The results show that the application of the proposed methodology considerably increases the oil recovery factor, thus corroborating its effectiveness in optimizing drilling operations. This research contributes significantly to reservoir engineering, providing a robust tool for the strategic planning of directional wells, and paves the way for future studies and applications in even more complex scenarios.